2022
DOI: 10.1097/dbp.0000000000001130
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Get SET Early Model in a Community Setting to Lower the Age of ASD Diagnosis

Abstract: Objective: The objective of this study was to implement a validated, university-based early detection program, the Get SET Early model, in a community-based setting. Get SET was developed to improve Screening, Evaluation, and Treatment referral practices. Specifically, its purpose was to lower the age of diagnosis and enable toddlers with autism spectrum disorder (ASD) to begin treatment by 36 months. Methods: One hundred nine pediatric health care providers were recruited to administer the Communication and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Studies have shown that implementing active screening programs can greatly aid in the early diagnosis of autistic children (17,19,54). Therefore, it is recommended that children undergo regular well-child care during the preschool period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that implementing active screening programs can greatly aid in the early diagnosis of autistic children (17,19,54). Therefore, it is recommended that children undergo regular well-child care during the preschool period.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is considerable variation in the age at which ASD is diagnosed across different countries. Although experienced clinicians are capable of diagnosing ASD in children before they reach the age of 2, the average age of diagnosis (AOD) reported internationally is between 4 and 5 years, indicating a signi cant delay in diagnosis (17)(18)(19)(20)(21)(22)(23)(24)(25). Despite these efforts, con icts and obstacles still exist in this eld (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…The overarching goal of the Get SET Early model was to lower the age of autism diagnosis and treatment starting at the pediatric level. In the parent study, a network of 109 pediatric healthcare professionals (PHPs) from 13 practices were recruited across the Phoenix metropolitan area and trained to implement a structured universal screening and referral procedure (see Smith et al, 2022). PHPs in the network agreed to screen universally at 12‐, 18‐, and 24‐month well‐visits using a standardized questionnaire, the Communication and Symbolic Behavior Scales Developmental Profile Infant–Toddler Checklist (ITC) (Wetherby & Prizant, 2002; Wetherby et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Participants included 646 toddlers who received developmental evaluations as part of a larger federally funded project assessing the feasibility of replicating a revised version of the 1-Year Well-Baby Check-Up Approachthe Get SET Early Model-in a new city (see Pierce et al, 2011Pierce et al, , 2021Smith et al, 2022). The overarching goal of the Get SET Early model was to lower the age of autism diagnosis and treatment starting at the pediatric level.…”
Section: Participantsmentioning
confidence: 99%